Lossless ROI Privacy Protection of H.264/AVC Compressed Surveillance Videos - Ma, Xiaojing; Zeng, Wenjun; Yang, Laurence T.; Zou, Deqing; Jin, Hai (Transactions on Emerging Topics in Computing, 2015)
Privacy becomes one of the major concerns of video surveillance systems, especially in cloud-based systems. Privacy protection of surveillance videos aims to protect privacy information without hampering normal video surveillance tasks. Region-of-interest (ROI) privacy protection is more practical compared with the whole video encryption approaches. However, one common drawback of virtually all current ROI privacy protection methods is that the original compressed surveillance video recorded in the camera is permanently distorted by the privacy protection process, due to the quantization in the re-encoding process. Thus, the integrity of the original compressed surveillance video captured by the camera is destroyed. This is unacceptable for some application scenarios, such as video forensics for investigations and video authentication for law enforcement. In this paper, we introduce a new paradigm for privacy protection in surveillance videos, referred to as lossless privacy region protection, which has the property that the distortion introduced by the protection of the privacy data can be completely removed from the protected videos by authorized users. We demonstrate the concept of lossless privacy region protection through a proposed scheme applied on H.264/Advanced Video Coding compressed videos.